Math Problem Statement
simplify (∼pvq)⇒(∼pvq)
Solution
To simplify the expression , we can follow these steps:
Step 1: Recognize the implication
The implication is logically equivalent to . Applying this to the given expression:
Step 2: Apply De Morgan's Law
We need to negate as part of the equivalence transformation:
Step 3: Substitute into the expression
Now substitute this back into the implication expression:
Step 4: Simplify using distribution
To simplify this further, we distribute the terms:
Using the tautologies and , we get:
Since anything is always , the entire expression simplifies to:
Thus, the simplified form of is True.
Would you like any more details or have questions?
Here are 5 related questions to consider:
- What is the difference between a tautology and a contradiction?
- How does De Morgan's law work with negations?
- What is the truth table for logical implications?
- Can all logical implications be simplified to True or False?
- How does logical equivalence relate to algebraic identities?
Tip: Logical equivalences can often be simplified by recognizing common tautologies and contradictions in their expressions.
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Logical Implication
Tautology
Formulas
A ⇒ B ≡ ∼A ∨ B
De Morgan's Law: ∼(p ∨ q) ≡ ∼p ∧ ∼q
Theorems
Tautology Theorem
De Morgan's Laws
Suitable Grade Level
Undergraduate Level (Introductory Logic/Discrete Math)
Related Recommendation
Logical Expression Simplification: ¬(q ⇒ ¬p) ⇒ (¬p ∨ q)
Logical Equivalence of ∼[(p ∨ r) → ∼(p ∨ q)] Explained
Solving the Logical Implication (p ∨ q) ∧ (~p) → q with the Law of Resolution
Establishing Logical Equivalence: p → ((p→q) ∧ ~ (~q ∨ ~p)) = ~p ∨ (q ∧ p)
Analyze Logical Argument: [(p ∨ q) ∧ (~p)] → q